2021
DOI: 10.1038/s41385-021-00376-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subverts the complement system in semen to enhance viral transmission

Abstract: Semen is important in determining HIV-1 susceptibility but it is unclear how it affects virus transmission during sexual contact. Mucosal Langerhans cells (LCs) are the first immune cells to encounter HIV-1 during sexual contact and have a barrier function as LCs are restrictive to HIV-1. As semen from people living with HIV-1 contains complement-opsonized HIV-1, we investigated the effect of complement on HIV-1 dissemination by human LCs in vitro and ex vivo. Notably, pre-treatment of HIV-1 with semen enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
(79 reference statements)
1
17
0
Order By: Relevance
“…effects in vivo as the transferred HIV virions should be complement-opsonized (17). Importantly, the effects seen in the tissues on the transcriptome and protein levels are not restricted to a direct infection of immune cells, but could also be attributed to the activation of PRRs and other innate pathways in the epithelial cells and immune cells that are exposed to but not productively infected by HIV but produce pro-inflammatory chemokines and anti-viral factors as shown by other groups (4,57,58).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…effects in vivo as the transferred HIV virions should be complement-opsonized (17). Importantly, the effects seen in the tissues on the transcriptome and protein levels are not restricted to a direct infection of immune cells, but could also be attributed to the activation of PRRs and other innate pathways in the epithelial cells and immune cells that are exposed to but not productively infected by HIV but produce pro-inflammatory chemokines and anti-viral factors as shown by other groups (4,57,58).…”
Section: Discussionmentioning
confidence: 90%
“…The female genital compartment contains an array of soluble factors that participate in local innate immune defenses; notable among them are complement proteins such as C1q and C3. During the initial phases of infection, the transferred HIV virions are opsonized by complement proteins (17) such as inactivated C3b (iC3b) and C1q that are attached to the viral surface (18). The complement protein C3 when activated forms C3b that can be part of the complement cascade that destroys pathogens or infected cells by cytolysis and virolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies implicated complement activation in HIV-1 infection enhancement ( 23 29 ). More recently, it has been reported that complement-opsonized virus promotes viral establishment in colorectal mucosa ( 30 ) and infection of mucosa-resident Langerhans cells ( 31 ). Evidence suggests that complement opsonization makes HIV-1 more accessible to host cells via interactions with complement receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The association of P80-mediated sustained MAPK phosphorylation with DC maturation and activation as well as the CTL-stimulatory capacity of P80-/HIV-exposed DCs has to be characterized in detail in a follow-up study. The P80-mediated antiviral effect observed in DCs in terms of complement-opsonized HIV-1 is critical as very recently Nijmeijer et al [ 25 ] illustrated that complement present in semen enhances HIV-1 infection of Langerhans Cells (LCs) that are the first immune cells encountering the virus during sexual contact. This process was mediated via binding to complement receptors 3 and 4 (CR3, CR4) and bypassing of langerin, thereby changing the restrictive nature of LCs into virus-disseminating cells [ 25 ] Targeting LCs and dermal DCs by P80 natural essence, which shows an antiviral as well as the antigen-presenting cell-boosting mechanism, provides thus a new tool to effectively prevent HIV-1 transmission at mucosal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The P80-mediated antiviral effect observed in DCs in terms of complement-opsonized HIV-1 is critical as very recently Nijmeijer et al [ 25 ] illustrated that complement present in semen enhances HIV-1 infection of Langerhans Cells (LCs) that are the first immune cells encountering the virus during sexual contact. This process was mediated via binding to complement receptors 3 and 4 (CR3, CR4) and bypassing of langerin, thereby changing the restrictive nature of LCs into virus-disseminating cells [ 25 ] Targeting LCs and dermal DCs by P80 natural essence, which shows an antiviral as well as the antigen-presenting cell-boosting mechanism, provides thus a new tool to effectively prevent HIV-1 transmission at mucosal surfaces. Moreover, plant-based HIV-VLPs were described that used plants for recombinant expression of HIV antigens to target mucosal immune responses [ 26 ].…”
Section: Discussionmentioning
confidence: 99%